2006
DOI: 10.1093/jxb/erl068
|View full text |Cite
|
Sign up to set email alerts
|

High-level tryptophan accumulation in seeds of transgenic rice and its limited effects on agronomic traits and seed metabolite profile

Abstract: Metabolic manipulation of plants to improve their nutritional quality is an important goal of plant biotechnology. Expression in rice (Oryza sativa L.) of a transgene (OASA1D) encoding a feedback-insensitive alpha subunit of rice anthranilate synthase results in the accumulation of tryptophan (Trp) in calli and leaves. It is shown here that the amount of free Trp in the seeds of such plants is increased by about two orders of magnitude compared with that in the seeds of wild-type plants. The total Trp content … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
60
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(70 citation statements)
references
References 39 publications
6
60
0
1
Order By: Relevance
“…Metabolomics studies in rice have so far demonstrated that the various metabolites can improve seed germination (Moongngarm and Saetung, 2010). The uniqueness of metabolites amongst wild type and mutant plants (Wakasa et al, 2006), the metabolome profiling at several phases of improvement (Tarpley et al, 2005), and the analysis of normal metabolite distinction amid altered rice varieties has been reported (Kusano et al, 2011).…”
Section: Plant Metabolomicsmentioning
confidence: 99%
“…Metabolomics studies in rice have so far demonstrated that the various metabolites can improve seed germination (Moongngarm and Saetung, 2010). The uniqueness of metabolites amongst wild type and mutant plants (Wakasa et al, 2006), the metabolome profiling at several phases of improvement (Tarpley et al, 2005), and the analysis of normal metabolite distinction amid altered rice varieties has been reported (Kusano et al, 2011).…”
Section: Plant Metabolomicsmentioning
confidence: 99%
“…The key rate-limiting enzyme in tryptophan synthesis is anthranilate synthase, which catalyzes the conversion of chorismate to anthranilate, and tryptophan levels in rice have been increased more than 400-fold by expressing a feedback-insensitive version (Wakasa et al 2006). Tryptophan levels also increased 30-fold in potato tubers (Yamada et al 2004) and 20-fold in soybean seeds (Ishimoto et al 2010) expressing feedback-insensitive AS.…”
Section: Essential Amino Acidsmentioning
confidence: 99%
“…Although there are complexities in the interpretation of data generated through modern profiling technologies (Broadhurst and Kell, 2006;Lay et al, 2006) including the fact that the data is not quantitative and there is no standardized framework for comparisons, the lack of variation between GM crops and their conventional comparators at the transcriptomic, proteomic, and metabolomic level has, nonetheless, been independently corroborated. These profiling evaluations extend to a wide range of plants including wheat (Baker et al, 2006;Gregersen et al, 2005;Ioset et al, 2007), potato (Catchpole et al, 2005;Defernez et al, 2004;Lehesranta et al, 2005), soybean (Cheng et al, 2008), rice (Dubouzet et al, 2007;Wakasa et al, 2006), tomato (Le Gall et al, 2003), tobacco, Arabidopsis (Kristensen et al, 2005), and Gerbera (Ainasoja et al, 2008).…”
Section: Information On Compositional Variation In Conventional Cropsmentioning
confidence: 99%